Finite element analysis of electromagnet actuator for non-contact modal testing - Muhamad Khusairi, Hassim (2012)
Chatter or self-excited vibration is always occurs during high speed machining operation. This phenomenon can reduce cutting tool life, poor surface finish on the machined component, and the possibility of serious damage to the machine itself. Before chatter stability can be predicted, modal testing is required to gain dynamic characteristic. This paper presents an analysis of initial design of EMA using Finite Element Analysis (FEA). This design of initial EMA will proper designed by using Magnetic Circuit Analysis (MCA) and Generalized Magnetic Theory (GMT). MCA is an analytical technique used to understand the magnetic flux characteristic of EMA, and GMT enabled predictions of the force capabilities based on the conservation of energy principle. The FEA software that will be used was the Finite Element Method for Magnetics (FEMM). Analysis result in the end can be displayed and plotted including flux path and density, and various field quantities. These methods predict that the actuator will produce sufficient force to create measurable deflection in cutting tools.